2016
DOI: 10.1080/23262133.2016.1231654
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ (PPARγ) activation: A key determinant of neuropathogeny during congenital infection by cytomegalovirus

Abstract: Congenital infection by human cytomegalovirus (HCMV) might result in permanent neurological sequelae, including sensorineural deafness, cerebral palsies or devastating neurodevelopmental abnormalities. We recently disclosed that Peroxisome ProliferatorActivated Receptor gamma (PPARg), a transcription factor of the nuclear receptor superfamily, is a key determinant of HCMV pathogenesis in developing brain. Using neural stem cells from human embryonic stem cells, we showed that HCMV infection strongly increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…During CMV infection, PPARγ levels are elevated in the fetal brain. In vitro studies showed that PPARγ expression increased in CMV-infected NSCs and is associated with less neuronal differentiation [ 85 , 98 ]. Treatment of CMV-infected NSCs with a PPARγ inhibitor rescued abnormal differentiation, demonstrating the potential of identifying druggable targets for restoring NSC function.…”
Section: Differentiation Of Nscsmentioning
confidence: 99%
“…During CMV infection, PPARγ levels are elevated in the fetal brain. In vitro studies showed that PPARγ expression increased in CMV-infected NSCs and is associated with less neuronal differentiation [ 85 , 98 ]. Treatment of CMV-infected NSCs with a PPARγ inhibitor rescued abnormal differentiation, demonstrating the potential of identifying druggable targets for restoring NSC function.…”
Section: Differentiation Of Nscsmentioning
confidence: 99%